Analysis of Primary Students’ Spatial Literacy on Reasoning - Sari, Elok Kartika; Ekawati, Rooselyna (Universitas Negeri Surabaya, 2018)
Spatial thinking is critical to mathematical thinking and achievement, important not only in mathematics learning and but also important in education research. In order to have similar opportunity in supporting primary students? spatial literacy on reasoning, it needs a clearer picture of primary students? spatial literacy on reasoning in solving Mathematical Literacy Tasks (MLT) as the aim of this study. The characteristic of MLT satisfies the PISA framework and considering Context, Content (shape and space), Process as well as level of problem. Researcher only focuses on three MLT problems. The result is about description of analyzing three participants? solution of MLT based on how they use kinds of spatial literacy on reasoning strategies. Dimensional reasoning is effective but the students didn?t use it often, the students seem like unfamiliar with these strategies. The responses suggest that because of the teacher didn?t use dimensional strategies in the class, so the student commonly didn?t use it often. Therefore, students need experiences that supporting their reasoning of spatial objects and its relationship and teacher can help students by using learning models, methods, or strategies in the class so their mathematical literacy (spatial literacy on reasoning) better than before.